2005
DOI: 10.1152/physiolgenomics.00096.2005
|View full text |Cite
|
Sign up to set email alerts
|

cDNA microarray analysis reveals novel candidate genes expressed in human peripheral blood following exhaustive exercise

Abstract: . cDNA microarray analysis reveals novel candidate genes expressed in human peripheral blood following exhaustive exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
1
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 54 publications
3
65
1
2
Order By: Relevance
“…These investigations (the FUNGENUT study) profiled gene expression in subcutaneous adipose tissue and found downregulation of IGF pathway genes and genes related to fat metabolism. Our results in prostate tissue were very similar; we also found down Recent studies also indicate that exercise may influence gene expression (42)(43)(44). These studies reported changes in gene expression in leukocytes after moderate or exhaustive exercise, with modulation of genes related to oxidative stress and inflammation.…”
Section: Discussionsupporting
confidence: 88%
“…These investigations (the FUNGENUT study) profiled gene expression in subcutaneous adipose tissue and found downregulation of IGF pathway genes and genes related to fat metabolism. Our results in prostate tissue were very similar; we also found down Recent studies also indicate that exercise may influence gene expression (42)(43)(44). These studies reported changes in gene expression in leukocytes after moderate or exhaustive exercise, with modulation of genes related to oxidative stress and inflammation.…”
Section: Discussionsupporting
confidence: 88%
“…In healthy subjects, aerobic conditioning increases the Th 1 response (8,26,42,65,68); however, its effect on the Th 2 response is poorly understood. Postulated immune mechanisms underlying allergic disease suggest that, in the general population, allergy should be less common in individuals with improved Th 1 response, since T lymphocytes would respond to antigen-presenting cells tending toward a Th 1 subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Postulated immune mechanisms underlying allergic disease suggest that, in the general population, allergy should be less common in individuals with improved Th 1 response, since T lymphocytes would respond to antigen-presenting cells tending toward a Th 1 subtype. We then hypothesized that anti-inflammatory effect due to aerobic training in chronic allergic airway inflammation could be mediated by improved Th 1 response and consequent reduced Th 2 response (8,26,32,42,65,68). However, in our experimental animal model, the OVA-induced increase in the expression of Th 2 cytokines (IL-4 and IL-5) was reduced by aerobic training, although the expression of Th 1 cytokines (IL-2 and IFN-␥) remained unchanged, suggesting that the anti-inflammatory effects of aerobic training in a murine model of lung allergic inflammation may occur due to a direct effect on the Th 2 response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABCA1 expression and abundance: The lymphocyte was powdered with cold mortar and pestle, and approximately 50 mg was used for the isolation of RNA. Total RNA was extracted by the guanidine thiocyanate method [25] and mRNA purified using an mRNA Isolation Kit (Roche, Germany) according to the manufacturer's instructions. Two-hundred nanograms of mRNA was used for synthesis of first strand cDNA by using oligo (dT) primer in the first-strand synthesis kit (Fermentase, Germany).…”
Section: Methodsmentioning
confidence: 99%